Penentuan Kawasan Kebisingan Bandara Polonia Medan - Ataline Muliasari (Research and Development Agency of The Ministry of Transportation, 2011)
Density rate of arrival and departure of aircraft would cause noise pollution and air area of the airport. Meanwhile, the international demands the maintenance of environmental conditions in the world.For people who live near the airport will certainly feel uncomfortable and unhealthy. ICAO (International Civil Aviation Organization) as the agency responsible for civil aviation is clearly not turning a blind eye on this. Thus enforcing the regulations limiting noise / noise limit. Until now, the area of airport noise is determined based on forecasts of aircraft, frequency and period of time aircraft operations.From the analysis shows that the Polonia Airport in Yogyakarta has a noise level (Weighted Equivalent Continuous Perceived Noise Level/WECPNL) 136,1175.